Fine-scale spatial partitioning of genetic variation and evolutionary contestability in the invasive estuarine mussel Xenostrobus securis. Issue 10 (26th November 2017) - Colgan, Donald J.
ABSTRACT: Initial studies of Australian populations of the widely invasive mussel Xenostrobus securis raised the possibility of non-random spatial partitioning within estuaries of mitochondrial DNA (mtDNA) clades that have dispersed intercontinentally and those that have not. A fine-scale phylogeographic investigation was made to examine this possibility using cytochrome c oxidase DNA sequences and data from five microsatellite loci developed here. X. securis in the study region was found to comprise multiple robustly supported mtDNA clades, many of which were genetically very distinct. Frequently, the clades comprised numerous haplotypes that have narrow ranges and may have evolved in situ within drainages or nearby. Microsatellite data reveal significant intra- and inter-drainage differentiation but at lower levels than mtDNA. Variation in mtDNA appears to reflect not only recolonization after infrequent local extinction within drainages but also the low probability of migratory haplotypes successfully establishing during evolutionary contests, with resident haplotypes having selective or demographic advantages derived from local occupation. The patterns of mtDNA haplotype distribution suggest that central New South Wales is the source of the internationally invasive lineages of X. securis .